Effects of Anisotropy and Supporting Configuration on Silicon Wafer Profile Measurements for Pattern Overlay Estimation. (16th September 2015) - Yoo, Woo Sik; Ishigaki, Toshikazu; Kang, Kitaek
Abstract : Wafer geometry and residual stress go through significant changes at different points in the semiconductor manufacturing process flow. Precise wafer geometry measurement is very important to assess process induced wafer geometry change (PIWGC) and minimize pattern overlay in lithography steps of advanced node devices and 3-D (3-dimensional) packaged devices. However, the precise wafer geometry measurement is very difficult due to gravitational wafer sag and interaction between the anisotropy of mechanical properties of Si and wafer supporting configurations. Effects of anisotropy and supporting configuration on 300 mm Si (001) wafer profile measurements were investigated for pattern overlay estimation and process optimization.